2015
DOI: 10.1016/j.bbmt.2015.07.029
|View full text |Cite
|
Sign up to set email alerts
|

High Disease-Free Survival with Enhanced Protection against Relapse after Double-Unit Cord Blood Transplantation When Compared with T Cell–Depleted Unrelated Donor Transplantation in Patients with Acute Leukemia and Chronic Myelogenous Leukemia

Abstract: Double-unit cord blood (DCB) grafts are a rapidly available stem cell source for adults with high-risk leukemias. However, how disease-free survival (DFS) after DCB transplantation (DCBT) compares to that of unrelated donor transplantation (URDT) is not fully established. We analyzed 166 allograft recipients (66 8/8 HLA-matched URDT, 45 7/8 HLA-matched URDT, 55 DCBT) aged 16–60 years with high-risk acute leukemia or chronic myelogenous leukemia (CML). URDT and DCBT recipients were similar except DCBT recipient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 55 publications
3
31
0
Order By: Relevance
“…For example, the University of Minnesota (UMN)/Fred Hutchinson Cancer Research Center (FHCRC) reported comparable 5-year disease-free survival (DFS) after myeloablative matched related, matched URD, mismatched URD and double unit CB (dCB) transplantation 4 . Recent single center comparisons has demonstrated comparable DFS in recipients of 8/8 HLA-matched URD and CB transplants (Figures 1A/1B) 6,8 . These analyses are notable for the low rates of relapse after CBT.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…For example, the University of Minnesota (UMN)/Fred Hutchinson Cancer Research Center (FHCRC) reported comparable 5-year disease-free survival (DFS) after myeloablative matched related, matched URD, mismatched URD and double unit CB (dCB) transplantation 4 . Recent single center comparisons has demonstrated comparable DFS in recipients of 8/8 HLA-matched URD and CB transplants (Figures 1A/1B) 6,8 . These analyses are notable for the low rates of relapse after CBT.…”
Section: Introductionmentioning
confidence: 89%
“…Our centers frequently prioritize a CB graft over a 7/8 HLA-matched URD and this practice is strongly supported by single center analyses 4,6,8 . Knowledge of the patient’s ancestry, use of computerized programs based upon population haplotype frequencies (eg the NMDP’s Haplogic and search prognosis tool 31,32 and consultation with HLA experts can rapidly determine the likelihood of identifying an 8/8 HLA-matched URD as soon as the recipients HLA-typing and preliminary search results are obtained.…”
Section: Graft Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…T-cell alloreactivity towards these precursor cells may result in unit predominance but also into enhanced graft versus leukemia (GVL) (22)(23)(24). Interestingly, in adult patients suffering from hematological malignancies, dUCBT may be associated with a lower incidence of relapse (25)(26)(27)(28)(29). A possible stronger graft versus leukemia (GvL) effect might be associated with a stronger T-cell mediated GVL reactivity, due to multiple major HLA-antigen mismatches (14,29).…”
Section: Summary Of Earlier Reported Resultsmentioning
confidence: 99%
“…4,5 Based on favorable outcomes in CBT recipients, we investigated this regimen in recipients of peripheral blood stem cells (PBSC) transplants. Twenty consecutive patients transplanted at Memorial Sloan Kettering Cancer Center between 2008 and 2013 who received Cy50/Flu150/Thio10/TBI400 were included in this retrospective analysis after obtaining approval from the center’s institutional review and privacy board.…”
mentioning
confidence: 99%